Hydrothermally etched MXene-based nanocomposite electrode for supercapattery - Wee Shen Loong N.; Liew J.; Pershaanaa M.; Farhana N.K.; Prasankumar T.; Bashir S.; Ramesh K.; Ramesh S. (Elsevier B.V., 2025)
The requirements of energy storage devices have only been ever-increasing, from greater charge storage to faster charging to boost the energy and power densities. However, existing lithium-ion batteries are limited by their power density due to long charging duration while supercapacitors have limited energy density and higher power density. A supercapattery, a device that possesses the qualities of a battery and a supercapacitor, is being developed to achieve higher energy and power densities in a single device. MXenes are a group of promising materials to be used as electrodes in supercapatteries for their exceptional pseudocapacitive properties. Herein, Ti3C2Tx MXene was synthesized using hydrothermal-assisted etching with various in situ HF etchants, and the effects of using different cationic intercalants were explored. This approach boosts the etching efficiency of weaker etchants, ensuring the proper exfoliation of MXene precursors whilst maintaining the structural integrity of MXenes and removing the need to delaminate and intercalate them post-synthesis. Combined with graphene by sonication, the resulting wrappage of graphene around MXene could increase the electrical conductivity, promote the electrode electrolyte interaction, and improve the electrochemical performance of MXene-based electrode signification and demonstrating synergistic effects. A supercapattery was fabricated by pairing activated carbon as the capacitive electrode and optimized MXene-graphene composite (MG-21) as the pseudocapacitive electrode. The device achieved a specific capacitance of 662.02F/g and an energy density of 20.58 Wh kg?1 at 3 A/g and exhibited an excellent energy and power density of 23.02 Wh kg?1 at 0.5 A/g and 13.1 kW kg?1 at 10 A/g, respectively. ? 2024 Elsevier B.V.